Behind the Saying “Landsbergis Destroyed the Collective Farms”: Transformation of Agriculture from the Perspective of Cultural Trauma Narrative - Budreckaitė, Valda (Politologija, 2023)
This article explores what is told about the supposed “collapse” of the collective farms in Lithuania, how is the negative connotation explained, and how is it attuned to the negative understanding of collectivization and collective farms in general. Relying on the theoretical literature dedicated to narrative and trauma, a scheme of cultural trauma narrative is formulated as a conceptual tool. Through narrative analysis of qualitative interviews collected in Panevėžys, Jonava, and their vicinities in 2021, it is demonstrated that the collective farm of early Soviet times is seen negatively, but the collective farm of late Soviet times is defined as a consistent unit. During transformation, this unit is suddenly disintegrated. Ordinary people are defined as the main victims. The named perpetrators can be divided into two groups. The first one is local people: the former chairs of the collective farms and other local leaders are mostly mentioned, as well as the “smarter ones” (“gudresnieji”). The second group is comprised of National government and Vytautas Landsbergis (personally); they are assigned a fatal role. A group of “critics” has been analytically distinguished. These informants have been harshly critical of collective farms regardless of times and distanced themselves from parlance regarding the “collapse” of collective farms. However, some of the “critics” repeated some elements of the cultural trauma narrative.